Recurrent primary leiomyosarcoma of the seminal vesicle treated with curative radiotherapy - Santacaterina, Anna; Scimone, Antonino; Parisi, Silvana; Settineri, Nicola; Platania, Angelo; Acquaviva, Grazia; Pergolizzi, Stefano (Bangladesh Journal of Medical Science, 2019)
A case of locally recurrent leiomyosarcoma of the left seminal vesicle, previously surgically resected, is described in a 65-year-old man. The patient underwent curative radiation therapy (61 Gy/33 fractions). Initially, he experienced a complete response after irradiation, but 15 months after treatment, progressive disease was recorded both in lung and bone, without evidence of local recurrence. The lack of efficient systemic therapies leads to a poor prognosis in this disease; clinical outcome in this patient seems to suggest the utility of radiotherapy in the very rare scenario of locally recurrent seminal vesicle leiomyosarcoma. Bangladesh Journal of Medical Science Vol.18(2) 2019 p.427-429